Intercultural Verbal and Nonverbal Communication Between Lembak and Javanese Communities in Rejang Lebong, Bengkulu - Robby Aditya Putra; Exsan Adde; Pajrun Kamil; Anrial Anrial; Ainul Mamnuah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This study aims to understand how the Lembak and Javanese communities interact amid significant language differences. The research was conducted in Rejang Lebong Regency, Bengkulu, focusing on both verbal and nonverbal interactions in daily life. Language and cultural value differences often pose challenges in intercultural communication. Using a descriptive qualitative approach, data were collected through participatory observation and in-depth interviews with members of both ethnic groups. Data analysis was conducted interactively, including data reduction, data presentation, and drawing conclusions. The findings reveal notable differences in verbal language use, specifically lexical ambiguities and "linguistic shock" caused by the distinct phonological endings of the Col dialect, which create initial communication barriers. Strategies to bridge these differences include using Indonesian as a lingua franca, joint language learning, and linguistic adaptation by migrants. Nonverbal communication through body gestures, facial expressions, and intonation also plays a crucial role, although cultural differences, such as the interpretation of direct eye contact as confrontational by Javanese or Javanese silence as indecisiveness by Lembak, can lead to misunderstandings. The study implies that cultural awareness, openness, and adaptive communication skills are key to fostering harmonious social interactions in multicultural societies.